copy number gain of the 6p arm is linked with advanced hepatocellular carcinoma: an array-based comparative genomic hybridization study - Chochi, Yasuyo; Kawauchi, Shigeto; Nakao, Motonao; Furuya, Tomoko; Hashimoto, Kiichiro; Oga, Atunori; Oka, Masaaki; Sasaki, Kohsuke (The Journal of pathology, 2009)
In accordance with cancer progression, genomic aberrations accumulate in cancer cells in a stepwise fashion. However, whether there are genomic changes linked with tumour progression remains unclarified. The purpose of this study is to elucidate the relationship between genomic alterations and clinical stages in hepatocellular carcinoma (HCC). A technology of array-based CGH using DNA chips spotted with 1440 BAC clones was applied to 42 surgically removed HCCs to examine the DNA copy number aberrations. A frequent copy number gain was detected on chromosomal regions 1q, 8q and Xq. In particular, gains of 1q42.12, 1q43 and 8q24.3 were detected in more than 65% of tumours. A frequent copy number loss was detected on chromosomal regions 1p, 4q, 6q, 8p and 17p. Losses of 8p21 and 17p13 were detected in more than 55% of HCCs. However, the DNA copy number gains of clones on 6p and 8q24.12 were more frequent in stage III/IV tumours than in stage I/II tumours (p < 0.001). In particular, the gain of the whole 6p was virtually limited to advanced-staged HCCs. The gain of the whole 6p is suggested to be a genomic marker for the late stages in HCCs. These observations therefore support the concept of genomic staging in HCC. Copyright © 2008 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.